Pengaruh Konsentrasi Natrium Karboksimetil Selulosa Terhadap Gel Hand Sanitizer Ekstrak Bunga Kecombrang (Etlingera elatior (Jack) R.M.Sm) (Studi Sifat Fisik dan Aktivitas Antibakteri Staphylococcus aureus) - Diana Akmaliyah Jamil (Fakultas Farmasi, 2024)
the effect of CMC Na concentration on physical properties (organoleptic, homogeneity, spreadability, viscosity, pH) and antibacterial activity of Staphylococcus aureus in hand sanitizer gel preparations of kecombrang flower extract (Etlingera elatior). The kecombrang flower simplicia was extracted using the maceration method with 96% ethanol solvent then continued with the phytochemical screening test stage to determine the compound content contained in the kecombrang flower extract. Hand sanitizer preparations were made using 3 formulas with each CMC Na concentration, namely F1 0.5%, F2 0.75%, and F3 1% and physical properties were evaluated including organoleptic tests, homogeneity, viscosity, pH, spreadability, and antibacterial activity test. The antibacterial activity test was carried out using the disk diffusion test method with chloramphenicol as a positive control, sterile water for injection as a negative control, and a hand sanitizer gel preparation of kecombrang flower extract without CMC Na as a comparative control. The data obtained was in the form of an evaluation of the physical properties and antibacterial activity of the kecombrang flower extract hand sanitizer gel preparation. Based on the results of data analysis carried out using the SPSS application, it shows that increasing the concentration of CMC Na in the hand sanitizer gel preparation of kecombrang flower extract (Etlingera elatior (Jack) R.M.Sm) can affect the physical properties of the preparation including increasing the viscosity value and pH value, decreasing the spreadability value, and has an insignificant effect on increasing the diameter of the inhibition zone against Staphylococcus aureus bacteria.
Reaploud Repository February 2026_Hasyim
Keywords: Etlingera elatior; Staphylococcus aureus; CMC-Na